Cyber Risk Management: Data Protection Strategies and Digital Security in Business - Loso Judijanto; Olyvia Rosalia (Maneggio, 2025)
This study aims to analyze the implementation of cyber risk management in companies and its impact on data protection and digital security. In a rapidly evolving digital era, cyber threats have become increasingly complex, compelling companies to adopt effective policies and security systems. This research uses a quantitative approach by collecting data through questionnaires distributed to company employees who are involved in managing information security systems. The results indicate that cyber risk management has a positive impact on the level of data protection and the company’s digital security. However, the biggest challenges faced by companies include limited budgets and a lack of cybersecurity professionals. In addition, large companies in the technology and financial sectors tend to have more mature policies and systems compared to small and medium-sized enterprises (SMEs). This study recommends that companies enhance regular evaluations and internal monitoring to improve the effectiveness of their implemented digital security strategies.